Disorders of Puberty in Girls - Sopher, Aviva B.; Oberfield, Sharon E.; Witchel, Selma F. (Seminars in Reproductive Medicine, 2021)
Puberty is the process through which reproductive competence is achieved and comprises gonadarche and adrenarche. Breast development is the initial physical finding of pubertal onset in girls and typically occurs between 8 and 13 years. Menarche normally occurs 2 to 3 years after the onset of breast development. Pubertal onset is controlled by the gonadotropin-releasing hormone pulse generator in the hypothalamus; however, environmental factors such as alterations in energy balance and exposure to endocrine-disrupting chemicals can alter the timing of pubertal onset. Improvement in nutritional and socioeconomic conditions over the past two centuries has been associated with a secular trend in earlier pubertal onset. Precocious puberty is defined as onset of breast development prior to 8 years and can be central or peripheral. Delayed puberty can be hypogonadotropic or hypergonadotropic and is defined as lack of breast development by 13 years or lack of menarche by 16 years. Both precocious and delayed puberty may have negative effects on self-esteem, potentially leading to psychosocial stress. Patients who present with pubertal differences require a comprehensive assessment to determine the underlying etiology and to devise an effective treatment plan.
Keywords: precocious puberty; delayed puberty; adrenarche; gonadarche